Power Restoration in Medium Voltage Network Using Multiagent System - Miroslav Kovac; Peter Bracinik; Marek Hoger; Marek Roch; Alena Otcenasova (Advances in Electrical and Electronic Engineering, 2013)
The article describes a novel approach to a power restoration in medium voltage power distribution network. It focuses primary at searching of a new network configuration enabling to minimalize the size of faulted area and to restore the power for the highest possible number of loads. It describes characteristic features of medium voltage power distribution network and discusses the implementation of the presented approach in existing networks. A software tool, developed by the authors, including physical simulation of model network and its autonomous control system is described. An example of fault situation in a virtual distribution network is presented. Afterwards, the solution of restoration problem by proposed multiagent system is simulated using the software tool described in the paper.